Risk factors associated with orthodontically induced root resorption: experimental study - Bianca Farias Amorim; Pedro Felipe Jesus Freitas; Aline Xavier Ferraz; Gabrielly Aparecida Eulalio dos Santos; Maysa Raksa Garcia; Bianca Simone Zeigelboim; Camila Paiva Perin; Cristiano Miranda de Araujo; Angela Graciela Deliga Schroder (Revista Sul-Brasileira de Odontologia, 2025)
Orthodontic tooth movement involves periodontal remodeling induced by mechanical forces, triggering an inflammatory response that facilitates bone resorption and deposition. However, orthodontically induced external apical root resorption (OIRR) is a frequent and undesirable side effect of treatment. Despite extensive research, its etiology remains unclear, with multiple intrinsic and extrinsic factors proposed as potential contributors. Objective: This study aimed to assess the risk factors associated with orthodontically induced root resorption through an experimental approach. Additionally, it sought to compare resorption levels between canines and premolars in cases with and without extractions. Material and methods: A sample of 37 orthodontic patients was analyzed, with 7 undergoing premolar extractions. Digital periapical radiographs were obtained at baseline and after treatment, and root resorption was classified according to the Levander and Malmgren index. Statistical analysis was performed using the Chi-square and Fisher’s Exact tests, with a significance level of 5%.Results: No significant differences were found in the degree of resorption between canines and premolars, regardless of extraction status (p > 0.05). However, all evaluated teeth exhibited some degree of resorption. Conclusion: Root resorption is a multifactorial process, and its occurrence was observed in all patients. Routine radiographic monitoring is essential, particularly for treatments exceeding six months, to minimize severe resorption risks and optimize treatment outcomes. Future studies should further investigate contributing factors to improve clinical management.